Endosperm cell death promoted by NAC transcription factors facilitates embryo invasion in Arabidopsis - Doll, Nicolas M.; Van Hautegem, Tom; Schilling, Neeltje; De Rycke, Riet; De Winter, Freya; Fendrych, Matyáš; Nowack, Moritz K. (Current biology, 2023)
In flowering plants, two fertilization products develop within the limited space of the seed: the embryo and the surrounding nutritive endosperm. The final size of the endosperm is modulated by the degree of embryo growth. In Arabidopsis thaliana, the endosperm expands rapidly after fertilization, but later gets invaded by the embryo that occupies most of the seed volume at maturity, surrounded by a single remaining aleurone-like endosperm layer.1,2,3,4 Embryo invasion is facilitated by the endosperm-expressed bHLH-type transcription factor ZHOUPI, which promotes weakening of endosperm cell walls.5,6 Endosperm elimination in zou mutants is delayed, and embryo growth is severely affected; the endosperm finally collapses around the dwarf embryo, causing the shriveled appearance of mature zou seeds.5,6,7 However, whether ZHOUPI facilitates mechanical endosperm destruction by the invading embryo or whether an active programmed cell death (PCD) process causes endosperm elimination has been subject to debate.2,8 Here we show that developmental PCD controlled by multiple NAC transcription factors in the embryo-adjacent endosperm promotes gradual endosperm elimination. Misexpressing the NAC transcription factor KIRA1 in the entire endosperm caused total endosperm elimination, generating aleurone-less mature seeds. Conversely, dominant and recessive higher-order NAC mutants led to delayed endosperm elimination and impaired cell corpse clearance. Promoting PCD in the zhoupi mutant partially rescued its embryo growth defects, while the endosperm in a zhoupi nac higher-order mutant persisted until seed desiccation. These data suggest that a combination of cell wall weakening and PCD jointly facilitates embryo invasion by an active auto-elimination of endosperm cells. [Display omitted] •Arabidopsis endosperm is actively eliminated by a programmed cell death process•Several redundantly acting NAC transcription factors promote programmed cell death•Ectopic NAC expression causes total endosperm elimination and aleurone-less seeds•Combining zhoupi and nac mutations causes endosperm persistence until desiccation Embryo and endosperm have to develop alongside each other in the confined space of the plant seed. Doll et al. reveal that invasive embryo growth during seed development is facilitated by an actively controlled endosperm cell death program in the model plant Arabidopsis thaliana.